Analysis of Essential Oil from Pericarps of Chimonanthus praecox - Cao, L.; Wu, B.H.; Wu, W.; Chen, L.; Hu, X.G.; Xu, Z.J.; Zheng, Y.L. (Asian Journal of Chemistry, 2012)
In this work, the essential oil from pericarps of Chimonanthus praecox was extracted by hydrodistillation and analyzed by gas chromatography-mass spectrometry (GC-MS). The essential oil in pericarps of both the wild and cultivated wintersweets were mainly characterized by sesquiterpenoids with more than 60 % and, shared 19 components, which indicated the close genetic relationship between the wild and cultivated wintersweets. At the same time, the outstanding differences of both yields and chemical components of the essential oils between the wild wintersweets from different populations, as well as between the wild and cultivated wintersweets, were observed. Pericarps of the tested wild wintersweets possessed higher essential oil contents and more abundant chemical components than those of the cultivated one, of which, the wild wintersweet at Qinghuazhen was more excellent than that at Taipingzhen, suggesting that partial genetic materials controlling some particular natural products might be varied and lost in the processes of evolution and domestication from wild to cultivated wintersweet and there are, to a certain extent, genetic diversity in wild wintersweets. These results revealed that the oil vacuole tissues of wintersweet flowers might be further developed to the fruits, even kept within the dried pericarps that are developed from the ovary walls, which implied that there are probably abundant oil vacuole cells in the pistil of wintersweet.